PENGARUH KOMPETENSI, INDEPENDENSI, PROFESIONALISME, PENGALAMAN DAN BEBAN KERJA AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI SURABAYA - Naurah Candra Aprilia; Rudi Pratono (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of auditor competence, auditor independence, auditor professionalism, auditor experience, and auditor workload on audit quality at Public Accounting Firms (PAFs) in Surabaya. The study employed a quantitative approach using primary data collected through questionnaires distributed to auditors working at Public Accounting Firms in Surabaya. The sampling technique used was purposive sampling, with the criteria that respondents had at least one year of work experience as auditors and were willing to participate in the study. The collected data were analyzed using multiple linear regression analysis with the assistance of Statistical Product and Service Solutions (SPSS) software. The results indicate that auditor competence, auditor independence, and auditor professionalism have a positive effect on audit quality. Auditors who possess strong knowledge, technical skills, objectivity, and professionalism tend to produce more reliable and higher-quality audits. Meanwhile, auditor experience and auditor workload do not have a significant effect on audit quality. Nevertheless, auditors continue to maintain the quality of audit results in accordance with auditing standards and professional codes of ethics, thereby producing audit reports that can be relied upon by users of financial statements.